Antiviral Drugs and Acute Kidney Injury (AKI) - Leowattana, Wattana (Infectious Disorders - Drug Targets, 2019)
The introduction of more efficient antiviral drugs are common cause drug-induced acute kidney injury (AKI). The true prevalence of antiviral drugs induced nephrotoxicity is hardly determined. It causes AKI by many mechanisms including acute tubular necrosis (ATN), allergic interstitial nephritis (AIN), and crystal nephropathy. ATN has been described with a few kinds of antiviral drugs such as cidofovir, adefovir and tenofovir with unique effects on transporter defects, apoptosis, and mitochondrial injury. AIN from atazanavir is a rapid onset of AKI and usually nonoliguric but dialytic therapy are needed because of severity. Additionally, crystal nephropathy from acyclovir, indinavir, and foscarnet can cause AKI due to intratubular obstruction. In this article, the mechanisms of antiviral drug-induced AKI were reviewed and strategies for preventing AKI were mentioned.
Keywords: adefovir